Piroplasmosis in wildlife: Babesia and Theileria affecting free-ranging ungulates and carnivores in the Italian Alps - Zanet, Stefania; Trisciuoglio, Anna; Bottero, Elisa; Fernández de Mera, Isabel G.; Gortázar, Christian; Carpignano, Maria G.; Ferroglio, Ezio (Parasites & Vectors, 2014)
[Background]: Piroplasmosis are among the most relevant diseases of domestic animals. Babesia is emerging as cause of tick-borne zoonosis worldwide and free-living animals are reservoir hosts of several zoonotic Babesia species. We investigated the epidemiology of Babesia spp. and Theileria spp. in wild ungulates and carnivores from Northern Italy to determine which of these apicomplexan species circulate in wildlife and their prevalence of infection. [Methods]: PCR amplification of the V4 hyper-variable region of the 18S rDNA of Babesia sp./Theileria sp was carried out on spleen samples of 1036 wild animals: Roe deer Capreolus capreolus (n = 462), Red deer Cervus elaphus (n = 52), Alpine Chamois Rupicapra rupicapra (n = 36), Fallow deer Dama dama (n = 17), Wild boar Sus scrofa (n = 257), Red fox Vulpes vulpes (n = 205) and Wolf Canis lupus (n = 7). Selected positive samples were sequenced to determine the species of amplified Babesia/Theileria DNA. [Results]: Babesia/Theileria DNA was found with a mean prevalence of 9.94% (IC95% 8.27-11.91). The only piroplasms found in carnivores was Theileria annae, which was detected in two foxes (0.98%; IC95% 0.27-3.49). Red deer showed the highest prevalence of infection (44.23%; IC95% 31.6-57.66), followed by Alpine chamois (22.22%; IC95% 11.71-38.08), Roe deer (12.55%; IC95% 9.84-15.89), and Wild boar (4.67%; IC95% 2.69-7.98). Genetic analysis identified Babesia capreoli as the most prevalent piroplasmid found in Alpine chamois, Roe deer and Red deer, followed by Babesia bigemina (found in Roe deer, Red deer and Wild boar), and the zoonotic Babesia venatorum (formerly Babesia sp. EU1) isolated from 2 Roe deer. Piroplasmids of the genus Theileria were identified in Wild boar and Red deer. [Conclusions]: The present study offers novel insights into the role of wildlife in Babesia/Theileria epidemiology, as well as relevant information on genetic variability of piroplasmids infecting wild ungulates and carnivores. This study was partially supported by funds from the ...